ZODIA SOAP AS REPELLENT AGAINST AEDES AEGYPTI MOSQUITOES - Simaremare, Eva Susanty (Brawijaya University, 2017)
Zodia is known as a native plant from Papua which is traditionally used as a mosquitoes repellent. The contents of zodia leaves are linalool and a-pinene which have been scientifically tested as a mosquitoes Aedes aegypti L repellent caused Dengue hemorrhagic fever (DHF). Essential oil of zodia has got by vapor distillation will be made as repellen in soap. The purpose of this research is to create a solid soap and mosquito repellent of zodia leaf (Evodia suaveolens Scheff) and to know the efficacy of the repellent against Aedes aegypti L. The results of this study indicated that the steam distilation process on this study produced 48,33 ml of the essential oils. The blue spot appeared on Thin Layer Chromatography (TLC) and the value of Rf is 0,3 indicated a linalool. All formulations produce good solid soap in terms of organoleptic, pH, ability to form foam and skin irritation tests. Solid soap with 1,5 ml zodia essensial oil was the most effective formula as Aedestaegypti L repellentfor two hours. The protection efficacy was reduced because the oil is volatile. Zodia soap was made successfully with white cream , aromatic smell, and solid phase. Soap has great foam, pH 8-9, homogeny, and non-irriating. The addition of concentration essential oils increase protection power as reppelent. With The addition of essential oils 1,5%, the protection power soap was 81% to mosquito Aedes aegypti L.